PROJECT MANAGEMENT INTRODUCTION FOR VILLAGE APPARATUS IN LANCANG GARAM VILLAGE, LHOKSEUMAWE - Fithri, Cut Azmah; Hassan, Soraya Masthura; Nasruddin, Nasruddin; Saputra, Eri (Universitas Muhammadiyah Aceh, 2022)
Non-governmental activities that carried out directly by the community are prone to have inappropriate management with the implementation both at the time of planning, field work and reporting. In the implementation of non-governmental activities, many problems arise related to governance in the filed and it is uncommon to have deal with laws to governance that in accordance with procedures. One of the efforts to avoid the inappropriate planning as well as managing activities is requiring the project management which includes planning, scheduling, and controlling. The expected outcome of this activity is the community and village officials can understand the objectives of the project management and direct implementation in managing the village activities. This activity was carried out in three steps, namely introduction to project management, introduction to work drawing/technical drawing and introduction to the budget calculation/RAB with participants which were village officials and the community of Gampong Lancang Garam, Banda Sakti, Lhokseumawe. Keywords: Project management, planning, controlling and supervision